(untitled) - DiOrio, Rana; Wheeler, Eliza (San Francisco, CA, 2010)
Teaches children about what it means to be present by discussing the important gift of appreciation, giving children and adults alike the opportunity to live more fully and richly.
Keywords: Generosity; Juvenile literature; Generosity; Juvenile literature; Gratitude; Kindness; Conduct of life; Juvenile literature; Mindfulness (Psychology); Gratitude; Juvenile literature; Thoughtfulness; Conduct of life; Juvenile literature; Kindness; Juvenile literature; Juvenile works; Picture books; Picture books; Childrens picture books